Pak Dogol and Wak Long in wayang kulit Kelantan / Mahmoud Dehghanharati - Mahmoud, Dehghanharati (2017)
This thesis focuses on the character analysis of Pak Dogol and Wak Long as clowns in wayang kulit Kelantan. The three objectives of this thesis are: 1) to explore the significance of the two clown characters, Pak Dogol and Wak Long, in wayang kulit Kelantan with focus on their myth origin, their role in wayang kulit stories and performances; 2) to investigate the characterization of Pak Dogol and Wak Long by exploring their visual features and possible origin with focus on their comic features; and 3) to investigate the comic qualities of these two characters as well as the comic methods used in wayang kulit Kelantan. Based on the objectives, the analysis of these two clown characters is done in four main aspects. The first is their significant and conventional definitions and myth origin both inside and outside of wayang kulit Kelantan. The second is the detailed analysis of the visual aspects of these characters as solely presented in their puppets in the wayang kulit Kelantan. The third aspect is the role of Pak Dogol and Wak Long in five selected stories and one wayang kulit performance script. In this aspect, the different roles of these clowns are explained in the stories and comic features in selected texts. Finally, the comic features of Pak Dogol and Wak Long is explained in the three recorded wayang kulit performances. However, four theories are applied in this thersis, these are, A- direct and indirect charactrization. B- Bakhtin theory of ggrotesque. C- postmodernism. D- interculaturalism. E- Bergson theory of comedy. In brief, Pak Dogol’s character as the main clown with a noble and divine origin is recognized by dalangs (puppeteers) who also consider him as a god-clown. His character is represented by a puppet with an ugly and exaggerated body shape which improves his clowning characteristic as well. In the selected stories, Pak Dogol takes on many roles such as a servant, guarder of other main characters such as Siti Dewi, consoler of Seri Rama and a clown with supernatural powers who can solve difficult problems. Moreover, Pak Dogol also provides situation comedy where necessary. Wak Long is the second clown character and loyal companion of Pak Dogol. Wak Long also is considered as a dignified and noble character by dalangs but still inferior to Pak Dogol. On the other hand, Wak Long’s character provides more comic features than Pak Dogol, especially in case of character and behavior comedy. Visually, Wak Long’s puppet design is similar to Pak Dogol but without as much exaggeration.